Deforestasi dalam Novel Jejak Balak Karya Ayu Welirang (Kajian Ekokritik Sastra): Deforestation in the Novel Jejak Balak by Ayu Welirang (A Study of Literary Ecocriticism) - Salsabila, Athaya; Meliasanti, Ferina; Muhtarom, Imam (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research is motivated by the massive reduction of forest cover. The reduction of forest cover is termed as deforestation. This research aims to analyze the driving factors of deforestation and the impact of deforestation in the novel Jejak Balak by Ayu Welirang using the perspective of literary ecocriticism. This research is a qualitative research that uses analytic descriptive method. The data collection techniques used in this research are reading technique, library technique, and note-taking technique. The results of the analysis of deforestation in the novel Jejak Balak by Ayu Welirang found; direct drivers of deforestation by human activities, namely illegal logging, forest burning and forest conversion; indirect drivers of deforestation, namely government policy failure, government weakness, and social, economic and politic factors; the impacts of deforestation include increased air temperature, flash floods, damage to housing, and the loss of living space for Indigenous peoples.